2013
DOI: 10.1002/ajh.23396
|View full text |Cite
|
Sign up to set email alerts
|

Double productive immunoglobulin sequence rearrangements in patients with chronic lymphocytic leukemia

Abstract: The immunoglobulin heavy chain variable (IGHV) gene mutational status represents a major prognostic marker in chronic lymphocytic leukemia (CLL). Usually, the prognostic implications of IGHV gene analysis can be reliably ascertained but, occasionally, double productive rearrangements have been detected. Clinical presentation and biological features of such cases are unknown. Sixty patients with morphologically and phenotypically monoclonal CLL but double productive IGHV rearrangements were retrospectively iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 43 publications
2
13
0
Order By: Relevance
“…This might be an explanation for recently published data indicating that patients with discordant status have an adverse clinical course similar to that of IGHV-unmutated cases. 43 Moreover, based on our observations, the gradual prevailing of one clone over other, also in cases with concordant status, was often accompanied by disease progression. We, therefore, advocate repeated testing of IGHV mutational status in MP-IGH CLL since it can indicated changes in disease behavior.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nsupporting
confidence: 51%
“…This might be an explanation for recently published data indicating that patients with discordant status have an adverse clinical course similar to that of IGHV-unmutated cases. 43 Moreover, based on our observations, the gradual prevailing of one clone over other, also in cases with concordant status, was often accompanied by disease progression. We, therefore, advocate repeated testing of IGHV mutational status in MP-IGH CLL since it can indicated changes in disease behavior.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nsupporting
confidence: 51%
“…In agreement with other studies 31,33,55 , we observed concordant IGHV mutational status of coexisting clones in almost two-thirds of oligoclonal cases (34/55; 62%). The remarkably high occurrence of concordant IGHV mutational status in oligoclonal cases suggests that coexisting clones experienced the same or similar influences affecting their development.…”
Section: Discussionsupporting
confidence: 93%
“…In published studies, oligoclonal CLL has been observed in 2 to 24.4% of cases, depending on the detection method used [31][32][33]54 . Prognostication of these oligoclonal cases may be challenging, especially in cases of coexisting clones with discordant IGHV mutational status 54 , and in this area, only limited work has so far been reported [31][32][33]55 . For the IGH rearrangement analysis within the current study, we used Sanger sequencing which has typically lower detection rate of multiple rearrangements.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been suggested that these combination regimens increase synergistically myelosuppression and immunosuppression, which comes to the prize of an increased risk of infections (66, 67). Severe or unusual infections, with higher rates of global infections compared with the historical group of patients treated with FC alone but without significant influence in infection-related mortality have been reported (62).…”
Section: Diagnosis and Therapy Issues Challenging The Role Of Preventmentioning
confidence: 99%